Scaffold‐mediated BMP‐2 minicircle DNA delivery accelerated bone repair in a mouse critical‐size calvarial defect model. Issue 8 (3rd June 2016) - Keeney, Michael; Chung, Michael T.; Zielins, Elizabeth R.; Paik, Kevin J.; McArdle, Adrian; Morrison, Shane D.; Ransom, Ryan C.; Barbhaiya, Namrata; Atashroo, David; Jacobson, Gunilla; Zare, Richard N.; Longaker, Michael T.; et al.
Abstract: Scaffold‐mediated gene delivery holds great promise for tissue regeneration. However, previous attempts to induce bone regeneration using scaffold‐mediated non‐viral gene delivery rarely resulted in satisfactory healing. We report a novel platform with sustained release of minicircle DNA (MC) from PLGA scaffolds to accelerate bone repair. MC was encapsulated inside PLGA scaffolds using supercritical CO2, which showed prolonged release of MC. Skull‐derived osteoblasts transfected with BMP‐2 MC in vitro result in higher osteocalcin gene expression and mineralized bone formation. When implanted in a critical‐size mouse calvarial defect, scaffolds containing luciferase MC lead to robust in situ protein production up to at least 60 days. Scaffold‐mediated BMP‐2 MC delivery leads to substantially accelerated bone repair as early as two weeks, which continues to progress over 12 weeks. This platform represents an efficient, long‐term nonviral gene delivery system, and may be applicable for enhancing repair of a broad range of tissues types. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2099–2107, 2016.